HOW TO TEACH THE DIFFERENCES BETWEEN PRESENT PERFECT AND PAST SIMPLE IN THE 11TH GRADE STUDENTS - Nuriddinova, Marjona (Educational Research in Universal Sciences, 2023)
This research paper explores an experimental approach to enhance the effective teaching of present perfect and past simple, aiming to avoid confusion between the two tenses in communication. The study was conducted with 11th-grade students at School N2 in Kasansay, Namangan. The paper provides guidance for instructing these tenses and offers suitable worksheets for students. Over a week, 10 students received topic-based gap filling handouts, and their daily results were recorded in a table. Notably, each student demonstrated noticeable improvement in utilizing both tenses in their communication. ESL teachers are recommended to adopt the instructions outlined in this paper to enhance their students’ grammar skills, particularly in mastering present perfect and past simple.